A citronellal-based polymer, a strong adhesion type citronellal-based super-hydrophobic coating and a preparation method thereof

CN121851336BActive Publication Date: 2026-09-01WUHAN TEXTILE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610136537.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-09-01
Estimated Expiration
2046-01-30

AI Technical Summary

Technical Problem

[0005]针对现有技术的缺陷,本申请的目的在于以香茅醇或香茅酸为原料提供一种能够与基底产生强粘附作用的生物基超疏水涂层,解决涂层附着力不足,在外力条件下容易开裂、剥落的问题

Benefits of technology

(1)首次采用开环聚合制备生物基香茅基聚合物,并以其构建疏水涂层,拓展了香茅类化合物的高值化应用领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121851336B_ABST
    Figure CN121851336B_ABST
Patent Text Reader

Abstract

The application belongs to the field of super-hydrophobic coating, and more particularly relates to a citronellal-based polymer, a strong-adhesion citronellal-based super-hydrophobic coating and a preparation method thereof. The application first converts citronellal into citronellyl norbornene formate or converts citronellic acid into citronellyl norbornene formate, then generates a low-surface-energy citronellal-based polymer through ring-opening polymerization, and further obtains a desired bio-based super-hydrophobic coating through the introduction of a micro-nano structure. The citronellal-based polymer used in the strong-adhesion super-hydrophobic coating has flexible citronellal side chains, which can promote the adhesion of the coating to the substrate; the ester bond in the side chains is easy to form a physical bond with the substrate, which can enhance the interfacial adhesion; and the cyclic structure in the polymer main chain can effectively improve the cohesion of the coating. The three synergistically bring excellent adhesion and mechanical durability to the super-hydrophobic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of superhydrophobic coatings, and more specifically, relates to a citronella-based polymer, a strong-adhesion citronella-based superhydrophobic coating, and a method for preparing the same. Background Technology

[0002] Superhydrophobic surfaces, functional materials inspired by natural wonders like lotus leaves and butterfly wings, are leading a wave of innovation in surface engineering with their exceptional physical properties. The most significant characteristic of these surfaces is their extremely high water contact angle (typically greater than 150°) and extremely low roll-off angle (less than 10°), making it difficult for droplets to spread and easy for them to roll off. Thanks to their superior water-repellent properties, superhydrophobic coatings have demonstrated significant application value in several key technology areas, including aircraft anti-icing, ship antifouling, self-cleaning, oil-water separation, and metal corrosion protection.

[0003] The successful preparation of superhydrophobic coatings relies heavily on the application of low surface energy compounds. For a long time, petroleum-based compounds, such as fluorinated compounds and long-chain aliphatic compounds, have been widely used to construct hydrophobic coatings due to their extremely low surface free energy and strong hydrophobic properties. However, these materials face severe sustainability challenges throughout their entire lifecycle, as their raw materials are highly dependent on non-renewable fossil fuels. Furthermore, fluorides pose potential hazards to the ecological environment and human health: they are difficult to degrade and easily accumulate in organisms, causing long-term ecological risks. Finally, these low surface energy substances often exhibit weak interactions with common substrates (such as metals, polymers, and ceramics), resulting in insufficient coating adhesion and poor mechanical strength. They are prone to failure under external forces such as wear, scratching, or impact. This inherent bottleneck in mechanical durability severely restricts their long-term service performance and application promotion under actual working conditions.

[0004] Biomass resources, with their unique advantages of being green, low-carbon, and renewable, are considered the only carbon source currently capable of large-scale replacement of fossil fuels. Citronellol and citronellolic acid are the main components of essential oils from more than 70 Rosaceae plants. They are non-grain biomass resources and are typical terpenoid compounds, with the structural formula shown below. Figure 1 As shown. Although this compound has been industrially produced, its downstream industries have long been limited to basic fragrances and essential oils in the daily chemical / food sectors. Therefore, transforming it into high-value-added functional materials is not only a core path to promote green transformation, but also a strategic tool for actively addressing climate change. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the purpose of this application is to provide a bio-based superhydrophobic coating that can strongly adhere to a substrate, using citronellol or citronellolic acid as raw materials. This solves the problems of insufficient coating adhesion and easy cracking and peeling under external force. Simultaneously, it provides new application areas for the high-value utilization of citronellol compounds.

[0006] To achieve the above objectives, according to a first aspect of the present invention, a method for preparing a citronellol-based polymer is provided, comprising the following steps: (1) Citronellol and 5-norbornene-2-carboxylic acid are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature to prepare polymerizable norbornene citronellol ester; or, citronellolic acid and 5-norbornene-2-methanol are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature to prepare polymerizable norbornene methyl ester. (2) The norborneol citronellyl ester or citronellyl methyl ester prepared in step (1) is mixed with the second catalyst and dissolved in an organic solvent. The ring-opening metathesis polymerization reaction occurs in a protective atmosphere. After the reaction is completed, the reaction is quenched and then precipitated in a poor solvent to obtain the citronellal polymer.

[0007] According to a second aspect of the present invention, a citronellol-based polymer prepared by the preparation method described above is provided.

[0008] According to a third aspect of the present invention, the application of the citronellol-based polymer described above in the preparation of superhydrophobic slurries or superhydrophobic coatings is provided.

[0009] According to a fourth aspect of the present invention, a strong adhesion citronella-based superhydrophobic slurry is provided, comprising the citronella-based polymer, and further comprising biowax, nanoparticles and an organic solvent; wherein the citronella-based polymer, biowax and nanoparticles are dispersed in the organic solvent, and the mass percentage of the citronella-based polymer in the slurry is 1% to 10%.

[0010] According to a fifth aspect of the present invention, a strong adhesion citronella-based superhydrophobic coating is provided, which is prepared by coating the citronella-based superhydrophobic slurry onto a substrate.

[0011] Overall, the technical solutions conceived in this application have the following beneficial effects compared with the prior art: (1) For the first time, ring-opening polymerization was used to prepare bio-based citronella polymers, and hydrophobic coatings were constructed using them, expanding the high-value application field of citronella compounds.

[0012] (2) The present invention prepares citronellol-based polymers using ring-opening metathesis polymerization (ROMP) technology, which has unique advantages such as mild reaction conditions and high polymerization activity. Norbornene (NB) is a common monomer for ROMP polymerization. Due to its bicyclic olefin structure, it can retain a rigid cyclic structure in the main chain after polymerization, giving the polymer unique mechanical properties.

[0013] (3) It is speculated that the citronellol-based polymer used in the strong adhesion superhydrophobic coating of the present invention has flexible citronellol side chains, which promotes the adhesion between the coating and the substrate; in addition, the ester bonds in the side chains are easy to form physical bonds with the substrate, which enhances the interfacial adhesion; while the cyclic structure in the polymer backbone can effectively improve the cohesiveness of the coating. The three factors work together to bring excellent adhesion and mechanical durability to the superhydrophobic coating.

[0014] (4) The low surface energy citronellol-based polymer in the strong adhesion superhydrophobic coating of the present invention uses bio-based citronellol or citronellolic acid as raw materials, which makes the superhydrophobic coating green and sustainable. Attached Figure Description

[0015] Figure 1 This is a molecular structure diagram of citronellol (content (a)) and citronellolic acid (content (b)).

[0016] Figure 2 This is a schematic diagram of the route for synthesizing bio-based citronellol or citronellolic acid as raw materials.

[0017] Figure 3 The norborneol citronellol monomer in Example 1 1 1H NMR spectrum (solvent: deuterated chloroform).

[0018] Figure 4 The citronellol-based polymer in Example 1 1 1H NMR spectrum (solvent: deuterated chloroform), GPC curve and molecular weight information.

[0019] Figure 5 The contact angles of Example 1 on different substrates (content (a)), the roll-off angle on a glass substrate (content (b)), and the contact angles of different liquids on the surface of Example 1 (content (c)) are shown.

[0020] Figure 6 The change in contact angle of Example 1 and Comparative Example 1 is shown as the number of times sandpaper is rubbed increases.

[0021] Figure 7 This is a schematic diagram of the surface coating, contact angle size, and evaluation level of Example 1 and Comparative Example 1 after a cross-cut test.

[0022] Figure 8 The graph shows the peel force curves for Example 1 and Comparative Example 1. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0024] The present invention provides a method for preparing a citronellol-based polymer, comprising the following steps: (1) Citronellol and 5-norbornene-2-carboxylic acid are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature to prepare polymerizable norbornene citronellol ester; or, citronellolic acid and 5-norbornene-2-methanol are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature (20-30℃) to prepare polymerizable norbornene methyl ester. (2) The norborneol citronellyl ester or citronellyl methyl ester prepared in step (1) is mixed with the second catalyst and dissolved in an organic solvent. The ring-opening metathesis polymerization reaction occurs in a protective atmosphere. After the reaction is completed, the reaction is quenched and then precipitated in a poor solvent to obtain the citronellal polymer.

[0025] In some embodiments, the molar ratio of citronellol to 5-norbornene-2-carboxylic acid in step (1) is 1.5:1 to 0.5:1; the molar ratio of 5-norbornene-2-methanol to citronellolic acid is 1.5:1 to 0.5:1. The catalyst in step (1) is dimethylaminopyridine p-toluenesulfonate (DPTS), and the dehydrating condensing agent is one or more of dicyclohexylcarbodiimide (DCC), diisopropylcarbodiimide (DIC), and 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC).

[0026] In some embodiments, the molar ratio of the dehydrating condensing agent to 5-norbornene-2-carboxylic acid or citronellolic acid in step (1) is 1:1 to 1.5:1, and the molar ratio of the first catalyst to 5-norbornene-2-carboxylic acid or citronellolic acid in step (1) is 0.05:1 to 0.2:1. The concentration of 5-norbornene-2-carboxylic acid in the reaction system of step (1) is 0.1-0.3 mol / L, the condensation reaction time is 15-20 hours, after the reaction is completed, the product is washed with water, and the product is further purified by column chromatography to obtain norbornene-citronellolic acid methyl ester or citronellolic acid norbornene-2-carboxylic acid methyl ester. The developing solvent used in the column chromatography is a mixture of ethyl acetate and petroleum ether, wherein ethyl acetate: petroleum ether = 1:8 to 1:30 ( v / v ).

[0027] In some embodiments, in step (2), the second catalyst is a Grubbs catalyst, the molar ratio of norbornene methyl ester or citronellol methyl ester to the Grubbs catalyst is 400:1 to 100:1; the concentration of the Grubbs catalyst is 1-5 mmol / L; the protective atmosphere is nitrogen and / or argon; the temperature of the ring-opening metathesis polymerization reaction is 40-80℃; and the reaction time is 8-16 hours.

[0028] In a preferred embodiment, the Grubbs catalyst in step (2) is one of the following catalysts: phenylmethimyl-[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolinyl]dichloro-(tricyclohexylphosphine)ruthenium (G2), dichloro[1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidene](benzylidene)bis(3-bromopyridine)ruthenium (II) (G3), dichloro(o-isopropoxyphenylmethylene)(tricyclohexylphosphine)ruthenium (II) (HG1), and dichloro[1,3-bis(2-methylphenyl)-2-imidazolidene](2-isopropoxyphenylmethylene)ruthenium (II) (HG2).

[0029] In some embodiments, the organic solvents used in steps (1) and (2) are independently one or more of anhydrous dichloromethane, chloroform, and ethyl acetate. The reaction is quenched with ethyl vinyl ether after step (2). The unsuitable solvents used in step (2) are methanol and / or ethanol.

[0030] The citronella-based polymer prepared by the method of this invention can be used to prepare superhydrophobic slurries or superhydrophobic coatings.

[0031] The present invention also provides a strong adhesion citronella-based superhydrophobic slurry, comprising the citronella-based polymer, and further comprising biowax, nanoparticles and organic solvent; wherein the citronella-based polymer, biowax and nanoparticles are dispersed in the organic solvent, and the mass percentage of the citronella-based polymer in the slurry is 1% to 10%.

[0032] In some embodiments, the mass ratio of the citronellol-based polymer, biowax, and nanoparticles is (1-4):(1-2):1.

[0033] In some embodiments, the citronellol-based polymer, biowax, and nanoparticles are mixed and then uniformly dispersed in an organic solvent by ultrasonic or magnetic stirring to obtain the citronellol-based superhydrophobic slurry.

[0034] In some embodiments, the biowax is one or more of carnauba wax, candelilla wax, soybean wax, rice bran wax, sugarcane wax, castor wax, white beeswax, beeswax, whale wax, and wool wax; The nanoparticles are one or more of the following: boehmite, montmorillonite, silica, titanium dioxide, carbon nanotubes, graphene, gold, and silver nanoparticles. The organic solvent is one or more of acetone, dichloromethane, trichloromethane, and ethyl acetate.

[0035] This invention first converts citronellol into norbornene citronellol ester or citronellolic acid into norbornene methyl ester, and then generates a low surface energy citronellol-based polymer (such as...) through a ring-opening polymerization reaction. Figure 2 (As shown). Further, by introducing micro / nano structures, the desired bio-based superhydrophobic coating is obtained. Therefore, this invention also provides a strongly adhering citronella-based superhydrophobic coating, which is prepared by coating the aforementioned citronella-based superhydrophobic slurry onto a substrate. In some embodiments, the coating is performed by scraping, brushing, spraying, or spin coating.

[0036] In some embodiments, a citronella-based superhydrophobic slurry is coated onto a substrate such as glass, paper, wood strips, tinplate, or cotton fiber, and then vacuum-dried to obtain the citronella-based superhydrophobic coating. Preferably, the vacuum drying temperature is 40-80°C, and the drying time is 2-6 hours.

[0037] The embodiments of the present invention are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally in accordance with conventional conditions.

[0038] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0039] The embodiments of this application are described below with reference to the accompanying drawings.

[0040] Example 1 (1) Citronellol and 5-norbornene-2-carboxylic acid were dissolved in dichloromethane at a molar ratio of 1.5:1 (where the concentration of 5-norbornene-2-carboxylic acid was 0.275 mol / L), and 0.1 equivalent of catalyst DPTS and 1.5 equivalent of condensing agent EDC were added sequentially. The mixture was reacted at room temperature for 18 hours to obtain polymerizable norbornene carboxylic acid citronellol. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:20 ( v / vThe product was purified by column chromatography using a solvent of [e.g., citronellol norborneol methyl ester] as the developing solvent. Example 1 prepared citronellol norborneol methyl ester... 1 H NMR spectrum as shown Figure 3 As shown.

[0041] 1 H NMR (600 MHz, CDCl3) δ = 6.21 – 6.13 (m, 1H), 6.11 – 5.90 (m, 1H), 5.12 – 5.05 (m, 1H), 4.17 – 3.99 (m, 2H), 3.23 – 3.00 (m, 1H), 2.96 – 2.87(m, 2H), 2.05 – 1.93 (m, 2H), 1.93 – 1.84 (m, 1H), 1.74 – 1.50 (m, 9H), 1.47 – 1.30 (m, 4H), 1.29 – 1.24 (m, 1H), 0.94 – 0.88 (m, 3H). (2) Citronellol norborneol carboxylate and G3 catalyst were added to a Schlenk flask at a molar ratio of 200:1, followed by the addition of an appropriate amount of anhydrous dichloromethane (G3 catalyst concentration was 2.5 mmol / L). Polymerization was carried out at 40°C under an argon atmosphere for 12 hours. After the reaction was completed, the reaction was quenched with 0.5 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent methanol. The citronellol-based polymer prepared in Example 1... 1 H NMR spectrum as shown Figure 4 As shown.

[0042] 1 H NMR (600 MHz, CDCl3) δ = 5.49 – 5.13 (m, 4H), 5.13 – 5.00 (m, 1H), 3.35 – 2.33 (m, 3H), 2.18 – 1.81 (m, 4H), 1.81 – 1.47 (m, 10H), 1.47 – 1.24(m, 3H), 1.17 (s, 1H), 0.97 – 0.82 (m, 3H). (3) The citronellol-based polymer, white beeswax and boehmite nanoparticles are mixed in a mass ratio of 1:1:1 and dispersed evenly in ethyl acetate by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the citronellol-based polymer is 10%.

[0043] (4) The slurry in (3) is loaded onto glass, paper, wood strips, tinplate and cotton fiber substrates by spin coating and vacuum dried at 60°C for 2 hours to obtain the desired bio-based superhydrophobic coating.

[0044] Example 2 (1) Citronellol and 5-norbornene-2-carboxylic acid were dissolved in dichloromethane at a molar ratio of 1.2:1 (where the concentration of 5-norbornene-2-carboxylic acid was 0.275 mol / L), and 0.05 equivalents of catalyst DPTS and 1.3 equivalents of condensing agent EDC were added sequentially. The mixture was reacted at room temperature for 24 hours to obtain polymerizable norbornene carboxylic acid citronellol. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:30 ( v / v The product was purified by column chromatography using 1000 ppm as the developing solvent to obtain citronellol norborneol carboxylic acid ester.

[0045] (2) Citronellol norborneol carboxylate and G2 catalyst were added to a Schlenk flask at a molar ratio of 100:1 (the concentration of G2 catalyst was 5 mmol / L), and an appropriate amount of anhydrous dichloromethane was added. Polymerization was carried out at 60°C under a nitrogen atmosphere for 16 hours. After the reaction was completed, the reaction was quenched with 1 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent ethanol.

[0046] (3) The citronella-based polymer, rice bran wax and TiO2 nanoparticles were mixed in a mass ratio of 4:1:1 and dispersed evenly in ethyl acetate by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the polymer was 8%.

[0047] (4) The slurry in (3) is applied to glass, paper, wood strips, tinplate and cotton fiber substrates by brushing. After vacuum drying at 80°C for 2 hours, the desired bio-based superhydrophobic coating is obtained.

[0048] Example 3 (1) Citronellol and 5-norbornene-2-carboxylic acid were dissolved in dichloromethane at a molar ratio of 1:1 (where the concentration of 5-norbornene-2-carboxylic acid was 0.275 mol / L), and 0.2 equivalents of catalyst DPTS and 1.2 equivalents of condensing agent DIC were added sequentially. The mixture was reacted at room temperature for 12 hours to obtain polymerizable norbornene carboxylic acid citronellol. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:10 ( v / v The product was purified by column chromatography using 1000 ppm as the developing solvent to obtain citronellol norborneol carboxylic acid ester.

[0049] (2) Citronellol norborneol carboxylate and HG1 catalyst were added to a Schlenk flask at a molar ratio of 400:1 (the concentration of HG1 catalyst was 1.25 mmol / L), and an appropriate amount of anhydrous chloroform was added. Polymerization was carried out at 80°C under a nitrogen atmosphere for 8 hours. After the reaction was completed, the reaction was quenched with 0.8 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent ethanol.

[0050] (3) The citronella-based polymer, beeswax, and SiO2 nanoparticles are mixed in a mass ratio of 2:1:1 and dispersed evenly in acetone by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the polymer is 6%.

[0051] (4) The slurry in (3) is sprayed onto glass, paper, wood strips, tinplate and cotton fiber substrates, and vacuum dried at 40°C for 4 hours to obtain the desired bio-based superhydrophobic coating.

[0052] Example 4 (1) Citronellol and 5-norbornene-2-carboxylic acid were dissolved in dichloromethane at a molar ratio of 0.8:1 (where the concentration of 5-norbornene-2-carboxylic acid was 0.275 mol / L), and 0.2 equivalents of catalyst DPTS and 1.1 equivalents of condensing agent DIC were added sequentially. The mixture was reacted at room temperature for 18 hours to obtain polymerizable norbornene carboxylic acid citronellol. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:8 ( v / v The product was purified by column chromatography using 1000 ppm as the developing solvent to obtain citronellol norborneol carboxylic acid ester.

[0053] (2) Citronellol norborneol carboxylate and HG2 catalyst were added to a Schlenk flask at a molar ratio of 200:1 (the concentration of HG2 catalyst was 2.5 mmol / L), and an appropriate amount of anhydrous chloroform was added. Polymerization was carried out at 60°C under an argon atmosphere for 12 hours. After the reaction was completed, the reaction was quenched with 0.5 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent methanol.

[0054] (3) The citronellol polymer, soybean wax and gold nanoparticles are mixed in a mass ratio of 4:2:1 and dispersed evenly in ethyl acetate by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the polymer is 4%.

[0055] (4) The slurry in (3) is spin-coated onto glass, paper, wood strips, tinplate and cotton fiber substrates, and vacuum dried at 40°C for 4 hours to obtain the desired bio-based superhydrophobic coating.

[0056] Example 5 (1) Citronellol and 5-norbornene-2-carboxylic acid were dissolved in dichloromethane at a molar ratio of 0.5:1 (where the concentration of 5-norbornene-2-carboxylic acid was 0.275 mol / L), and 0.1 equivalent of catalyst DPTS and 1 equivalent of condensing agent DCC were added sequentially. The reaction was carried out at room temperature for 24 hours to obtain polymerizable norbornene carboxylic acid citronellol. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:20 ( v / v The product was purified by column chromatography using 1000 ppm as the developing solvent to obtain citronellol norborneol carboxylic acid ester.

[0057] (2) Citronellol norborneol carboxylic acid ester and HG1 catalyst were added to a Schlenk flask at a molar ratio of 150:1 (the concentration of HG1 catalyst was 3.33 mmol / L), and an appropriate amount of anhydrous ethyl acetate was added. Polymerization was carried out at 40°C under a nitrogen atmosphere for 16 hours. After the reaction was completed, the reaction was quenched with 0.8 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent methanol.

[0058] (3) The citronellol polymer, palm wax and graphene are mixed in a mass ratio of 1:2:1 and dispersed evenly in dichloromethane by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the polymer is 2%.

[0059] (4) The slurry in (3) is applied to glass, paper, wood strips, tinplate and cotton fiber substrates by scraping and drying in vacuum at 60°C for 2 hours to obtain the desired bio-based superhydrophobic coating.

[0060] Example 6 (1) 5-norbornene-2-methanol and citronellolic acid were dissolved in dichloromethane at a molar ratio of 1.2:1 (where the concentration of citronellolic acid was 0.275 mol / L), and 0.05 equivalents of catalyst DPTS and 1.2 equivalents of condensing agent EDC were added sequentially. The reaction was carried out at room temperature for 12 hours to obtain polymerizable citronellolic acid norbornene methyl ester. After the reaction was completed, the product was washed with water and further purified with ethyl acetate:petroleum ether = 1:30 ( v / v The product was purified by column chromatography using 1000 mol / L as the developing solvent to obtain citronellol norbornene methyl ester.

[0061] (2) Citronellol methyl ester and G2 catalyst were added to a Schlenk flask at a molar ratio of 400:1 (the concentration of G2 catalyst was 1.25 mmol / L), and an appropriate amount of anhydrous chloroform was added. Polymerization was carried out at 80 °C under an argon atmosphere for 8 hours. After the reaction was completed, the reaction was quenched with 1 mL of ethyl vinyl ether, and the citronellol-based polymer was obtained after precipitation in the unsuitable solvent methanol.

[0062] (3) The citronellol polymer, wool wax and carbon nanotubes are mixed in a mass ratio of 2:2:1 and dispersed evenly in dichloromethane by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of the polymer is 1%.

[0063] (4) The slurry in (3) is applied to glass, paper, wood strips, tinplate and cotton fiber substrates by scraping and drying in vacuum at 80°C for 2 hours to obtain the desired bio-based superhydrophobic coating.

[0064] Comparative Example (1) White beeswax and boehmite nanoparticles were mixed at a mass ratio of 1:1 and dispersed evenly in dichloromethane by ultrasonic and magnetic stirring as a slurry, wherein the mass fraction of white beeswax was 10%.

[0065] (2) The slurry in (1) is spin-coated onto glass, paper, wood strips, tinplate and cotton fiber substrates, and vacuum dried at 60°C for 2 hours to obtain the desired bio-based superhydrophobic coating.

[0066] Performance testing The norborneol citronellol ester and citronellol polymer from Example 1 were dissolved in deuterated chloroform (CDCl3), and tetramethylsilane (TMS) was used as an internal standard for chemical shift. The samples were then analyzed using a Bruker Avance 600 nuclear magnetic resonance spectrometer. 1 1H NMR (600 MHz) spectrum. (See attached image.) Figure 3 As shown, due to the presence of endogenous ( endo ) and appearance ( EXO Two isomers, with hydrogen atoms in different chemical environments, exhibit two sets of signals in the spectrum, but the sum of their integrated areas is close to the theoretical integer, consistent with expectations. Compared with the monomer spectrum, the polymer's 1H NMR spectrum... Figure 4 The chemical shift of the signals corresponding to hydrogen atoms at positions 1 and 2 in the polymer matrix shifted from approximately 6.0 ppm to around 5.3 ppm, demonstrating the successful preparation of the polymer. Furthermore, Figure 4 The significant broadening of the mid-hydrogen spectrum signal also proves the successful transformation of monomer into polymer.

[0067] The number-average molecular weight of polymers was measured using a polymer laboratory gel permeation chromatography (PL GPC50) equipped with three PL gel mixing C-columns. M n ) and dispersion ( Ð Each injection was of a polymer solution (100 μL, with a concentration of 1 mg / mL in THF). -1 ). In THF (flow rate: 1 mL min) -1 In 35 oMeasurements were performed at C using a Waters 1525 binary HPLC pump equipped with a Waters 2414 refractive index detector. Several narrow-dispersion polystyrene ( M n = 1.3-900.0 kDa; Ð =1.06-1.10) was used as an internal standard, and calculations were performed using Breeze 3.30 SPA software. M n and Ð Value. For example... Figure 4 As shown, the elution time of the obtained product was concentrated in the 7-8 minute range, which is significantly earlier than the expected position of the monomer molecule, indicating a substantial increase in the product molecular size. The number-average molecular weight (Mn) was 45.4 kDa, representing an increase of several orders of magnitude compared to the monomer, providing conclusive quantitative evidence for polymerization. Although the molecular weight distribution was relatively broad (PDI = 2.47), this may be due to differences in polymerization kinetics caused by the presence of endogenous / exogenous isomers in the norbornene monomer. However, the single polymer main peak was clearly visible in the spectrum and was completely separated from possible small molecule impurity peaks, further demonstrating the successful synthesis of the target polymer.

[0068] All wettability tests were conducted at room temperature and normal pressure using a professional contact angle measuring instrument (model: JSC, Beijing Zhongyi Kexin Technology Co., Ltd.). For static contact angle measurements, approximately 5 μL of test droplet (distilled water or a specified liquid) was deposited on the sample surface using a micro-syringe. The droplet profile image was captured by the instrument's high-speed camera, and the static contact angle was calculated using the Young-Laplace fitting algorithm. Measurements were taken at least three different locations for each sample, and the average value was used as the final result. For roll-off angle measurements, the sample was placed horizontally on a platform with precisely controllable tilt angle, and approximately 10 μL of water droplet was placed on its surface. The platform tilt angle was then slowly increased at a rate of approximately 1° / s, and the tilt angle at the moment the water droplet began to roll was recorded as the roll-off angle of that surface. Measurements were repeated three times for each sample, and the average value was used. Figure 5 As shown, the slurry prepared in Example 1 has a contact angle greater than 150° on various substrates, including glass, paper, wood strips, tinplate, and cotton fibers. Figure 1 Content (a)). Additionally, we found that Example 1 has a small roll angle, such as Figure 1 As shown in section (b), the roll-off angle is 1~3° for a glass substrate. It can be seen that the introduction of low surface energy citronellol polymer can achieve superhydrophobicity of the coating. Figure 5 Content (c) shows photographs and contact angle values ​​of non-pure water droplets such as tea, salt water, milk, Sprite, and Coca-Cola added to the coating surface, indicating that Example 1 can exhibit good superhydrophobic properties for a variety of droplets.

[0069] A sandpaper friction and wear test was used to simulate surface mechanical loss to evaluate the wear resistance and durability of the coating. 800-grit silicon carbide standard sandpaper was selected as the friction pair and fixed flat on a horizontal platform. A 100g weight was applied to the surface of the coated sample as a load, bringing the sandpaper into contact with the coating surface under constant pressure. The sample was driven to reciprocate relative to the sandpaper at a fixed speed, with a single stroke of 10 cm. Each complete reciprocating motion was counted as one friction cycle. The above friction test was performed on the coating samples of Example 1 and Comparative Example 1, respectively, and the static water contact angle of their surfaces was measured after different numbers of friction cycles. The results are as follows: Figure 6 As shown, the coating prepared in Example 1 retains significant superhydrophobic properties even after 100 rubs, while the contact angle of Comparative Example 1 drops to approximately 120° after 20 rubs. This indicates that the introduction of the citronellol-based polymer improves the mechanical durability of the coating.

[0070] The adhesion performance between the coating and the substrate was evaluated according to the standard cross-cut adhesion test method. A cross-cut adhesion tester with a blade spacing of 1 mm was used to apply even pressure smoothly to the coating surface, cutting parallel lines in two mutually perpendicular directions to form an orthogonal grid. During cutting, the blade should penetrate the coating until it reaches the substrate surface. A transparent pressure-sensitive adhesive tape (3M #600 tape) meeting the standard requirements was used and firmly adhered to the grid area. The back of the tape was repeatedly rubbed with a finger or eraser to ensure full contact with the coating and no air bubbles. Finally, the tape was quickly and smoothly peeled off at a 60° angle to the surface, and the coating peeling in the grid area was observed. The adhesion grade of each sample was evaluated and recorded according to the standard grading standard from 0B (no peeling) to 5B (peeling area > 65%). In the areas after cross-cut adhesion and tape peeling, the static water contact angle was measured using a contact angle meter and compared with the original contact angle of the un-crossed areas. Figure 7 As shown, in Example 1, no coating peeling or separation was observed at the intersections of the scratches or at the edges of the scratches. After the tape was peeled off, no coating fragments adhered to the tape, and the coating in the test area remained intact, achieving a level 0 standard. In contrast, in Comparative Example 1, the coating peeled off, covering an area of ​​50%, achieving a level 4 standard. This indicates that the introduction of the bio-based citronellol polymer improved the adhesion between the coating and the substrate, thereby enhancing scratch resistance.

[0071] Following the standard peel test method (ASTM D6862), a peel force testing machine was used to quantitatively evaluate the interfacial adhesion performance of the coating. A standard pressure-sensitive adhesive tape (3M #610) with a width of 25 mm was selected, and one end was firmly adhered to the coating surface, ensuring no air bubbles. A standard pressure roller was used to roll back and forth on the tape three times at a constant speed and pressure to ensure sufficient adhesion. A universal testing machine equipped with peel test fixtures was used. The sample substrate was fixed in the lower fixture, and the free end of the tape was folded vertically upwards and clamped in the upper fixture, so that the tape and the coating surface formed a 180° angle. The fixture separation speed was set to 200 mm / min, and the instrument recorded the force changes during the peeling process in real time. The average force value during the stable phase of the peeling process (usually excluding the initial and final peak values) was taken to calculate the peel force (unit: N). A typical force-displacement curve is shown below. Figure 8 As shown, Example 1 exhibits a higher average peel force of 0.179 N, indicating a stronger bond between its coating and the substrate; while Comparative Example 1 shows a lower peel force of 0.029 N, indicating weaker coating adhesion. This is mainly due to the improved adhesion between the coating and the substrate resulting from the introduction of the bio-based citronellol polymer.

[0072] The hydrophobic coatings prepared in Examples 2 to 6, under the same conditions, showed contact angles higher than 150° on various substrates including glass, paper, wood strips, tinplate, and cotton fibers, and roll-off angles of 1 to 10° on the substrates. After 100 cycles of friction, they still maintained significant superhydrophobic properties, and the average peel force measured by the standard peel test method was in the range of 0.179-0.138 N.

[0073] In summary, the citronella-based polymer prepared in the embodiments of the present invention can improve the adhesion between the coating and the substrate, thereby improving the coating's resistance to friction and scratching. This may be mainly related to the high adhesion caused by the polymer's structure: (1) the flexible citronella side chains can reduce the glass transition temperature ( T g (1) Promotes adhesion to the substrate; (2) Ester bonds in the side chain easily form physical bonds with the substrate, enhancing interfacial adhesion; (3) The cyclic structure in the polymer main chain can effectively enhance the cohesiveness of the coating.

[0074] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing a citronellol-based polymer, characterized in that, Includes the following steps: (1) Citronellol and 5-norbornene-2-carboxylic acid are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature to prepare polymerizable norbornene citronellol ester; or, citronellolic acid and 5-norbornene-2-methanol are mixed and dissolved in an organic solvent, and a first catalyst and a dehydrating condensing agent are added. A condensation reaction is carried out at room temperature to prepare polymerizable norbornene methyl ester. (2) The norborneol citronellyl ester or citronellyl methyl ester prepared in step (1) is mixed with the second catalyst and dissolved in an organic solvent. The ring-opening metathesis polymerization reaction occurs in a protective atmosphere. After the reaction is completed, the reaction is quenched and then precipitated in a poor solvent to obtain the citronellal polymer.

2. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of citronellol to 5-norbornene-2-carboxylic acid is 1.5:1 to 0.5:1; the molar ratio of 5-norbornene-2-methanol to citronellolic acid is 1.5:1 to 0.5:

1. Step (1) The first catalyst is dimethylaminopyridine p-toluenesulfonate, and the dehydrating condensing agent is one or more of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide.

3. The preparation method according to claim 1, characterized in that, Step (2) The second catalyst is a Grubbs catalyst, and the molar ratio of citronellol norbornyl methyl ester or citronellol norbornyl methyl ester to the Grubbs catalyst is 400:1~100:1; The protective atmosphere is nitrogen and / or argon, and the ring-opening metathesis polymerization reaction is carried out at a temperature of 40-80°C for 8-16 hours.

4. The citronellol-based polymer prepared by the preparation method according to any one of claims 1 to 3.

5. The application of the citronellol-based polymer as described in claim 4 in the preparation of superhydrophobic slurries or superhydrophobic coatings.

6. A strongly adhesive citronella-based superhydrophobic slurry, characterized in that, The slurry includes the citronellol-based polymer as described in claim 4, and further includes biowax, nanoparticles, and an organic solvent; wherein the citronellol-based polymer, biowax, and nanoparticles are dispersed in the organic solvent, and the mass percentage of the citronellol-based polymer in the slurry is 1% to 10%.

7. The citronella-based superhydrophobic slurry as described in claim 6, characterized in that, The mass ratio of the citronella-based polymer, biowax, and nanoparticles is (1-4):(1-2):

1.

8. The citronella-based superhydrophobic slurry as described in claim 6, characterized in that, The biowax is one or more of the following: carnauba wax, candelilla wax, soybean wax, rice bran wax, sugarcane wax, castor wax, white beeswax, beeswax, whale wax, and wool wax; The nanoparticles are one or more of the following: boehmite, montmorillonite, silica, titanium dioxide, carbon nanotubes, graphene, gold, and silver nanoparticles. The organic solvent is one or more of acetone, dichloromethane, trichloromethane, and ethyl acetate.

9. A strongly adhesive citronella-based superhydrophobic coating, characterized in that, It is prepared by coating a substrate with the citronella-based superhydrophobic slurry as described in any one of claims 6 to 8.

10. The citronella-based superhydrophobic coating as described in claim 9, characterized in that, The coating is applied by scraping, brushing, spraying, or spin coating.

Citation Information

Patent Citations

  • Polyolefin containing thymine and preparation method and application thereof

    CN121378682A

  • Crosslinked cyclic olefin resin film, laminate and production method of laminate

    JP2014098058A